2023
DOI: 10.3390/foods12132518
|View full text |Cite
|
Sign up to set email alerts
|

Applications of Enzyme Technology to Enhance Transition to Plant Proteins: A Review

Abstract: As the plant-based food market grows, demand for plant protein is also increasing. Proteins are a major component in foods and are key to developing desired structures and textures. Seed storage proteins are the main plant proteins in the human diet. They are abundant in, for example, legumes or defatted oilseeds, which makes them an excellent candidate to use in the development of novel plant-based foods. However, they often have low and inflexible functionalities, as in nature they are designed to remain den… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 161 publications
0
7
0
Order By: Relevance
“…In general, seed storage proteins can be classified based on solubility; they include water-soluble albumins, salt-soluble globulins, hydrophobic prolamins which are commonly soluble in 70% ethanol, and glutenin primarily extracted using acidic solvents or alkali [59,60]; however, some quantity of protein may remain unextracted if not soluble in these solvents [61]. The protein fractions derived from HSC primarily comprise edestin (globulin), which constitutes approximately 60-80%, while albumin around 25% [62]. PSC consists of 87% extractable proteins (glutelin 49%, globulin 20.4%, albumin 13.5%, and prolamin 4.3%) [63] and FSC (albumin 38.1%, glutelin 33.9%, and globulin 27.9%) [64].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In general, seed storage proteins can be classified based on solubility; they include water-soluble albumins, salt-soluble globulins, hydrophobic prolamins which are commonly soluble in 70% ethanol, and glutenin primarily extracted using acidic solvents or alkali [59,60]; however, some quantity of protein may remain unextracted if not soluble in these solvents [61]. The protein fractions derived from HSC primarily comprise edestin (globulin), which constitutes approximately 60-80%, while albumin around 25% [62]. PSC consists of 87% extractable proteins (glutelin 49%, globulin 20.4%, albumin 13.5%, and prolamin 4.3%) [63] and FSC (albumin 38.1%, glutelin 33.9%, and globulin 27.9%) [64].…”
Section: Discussionmentioning
confidence: 99%
“…An industry-relevant extraction is considered a salt extraction (known as micellization), which is considered a milder extraction associated with less structural and conformationchanges [61]. It affects solubility by altering the electrostatic interactions (ionic strength) promoting aggregation [62]. Alkali extraction is widely used at an industrial level; it is suggested that the use of alkali can disrupt disulfide cross-linking in proteins and to ionize neutral and acidic amino acids, therefore increasing solubility [62].…”
Section: Discussionmentioning
confidence: 99%
“…Following extraction, processing techniques are employed to concentrate and purify seaweed proteins for various applications. Ultrafiltration, a popular method, utilizes membranes with specific pore sizes to concentrate proteins while removing unwanted impurities and contaminants [ 105 ]. Precipitation methods, such as salting out and acid precipitation, selectively precipitate proteins based on their solubility characteristics, allowing for further purification [ 106 ].…”
Section: Algae Proteins and Amino Acidsmentioning
confidence: 99%
“…Continued research is needed to better understand the nutritional composition, functional properties, and health benefits of seaweed proteins. Innovation in extraction methods, processing technologies, and product formulation will drive the development of novel seaweed-based products with improved taste, texture, and functionality [ 8 , 105 ].…”
Section: Applications Of Seaweed Proteins In Food Products Dietary Su...mentioning
confidence: 99%
“…When looking for ways to create structures and materials using biopolymer-based systems that are completely biodegradable, it is worth taking a look at other disciplines such as agronomy and food science. Here, material development and modification is often performed by enzymes covering a wide range of different classes of raw materials and polymers, ranging from lignins and fiber-based residues to protein-rich matrices [22][23][24]. Enzymes can be regarded as proteinogenic catalyzers that enable chemical reactions by lowering the activation energy.…”
Section: Introductionmentioning
confidence: 99%